The Relationship Between Level With The Online Teaching Learning Process For Napsiah Health Vocational School Students In The Covid-19 Pandemic Stabat – Langkat 2021 - Amri, Siskawati (Sekolah Tinggi Ilmu Kesehatan Putra Abadi Langkat, 2021)
The saturation level is a very deep pressure that has reached the saturation point. Online learning is a method of learning or distance learning using sophisticated information and communication technology in the digital era. This type of research is a descriptive study using a cross-sectional analytic study design. The purpose of the research is to determine the relationship between the level of saturation and the online teaching and learning process of SMK KesehatanNapsiah students in the Covid-19 Pandemic Period 2021. In this study, the sampling technique used was The sample was carried out using a total sampling technique of 36 people. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000< 0.05) then H0 is rejected so it can be concluded that there is a relationship between the level of saturation and the online teaching and learning process for SMK KesehatanNapsiah students in during the Covid-19 Pandemic. pay more attention to the online learning process whether it is good or not to be applied.